Improving student health literacy through a health book exhibition at Muhammadiyah junior high school in Kendari - La Ode Liaumin Azim; Agnes Mersatika Hartoyo (Indonesian Red Crescent Humanitarian Journal, 2025)
Health literacy plays an important role in shaping healthy behaviors among adolescents; however, the level of health literacy among junior high school students in Indonesia remains low. Initial assessments at Muhammadiyah Kendari Junior High School indicated that most students (73%) had insufficient knowledge of health information and rarely used health books as learning resources. This study aimed to improve students’ health literacy through a health book exhibition intervention conducted as part of community service activities. The study employed a pre-experimental design using a one-group pretest–posttest approach involving 30 students at SMP Muhammadiyah Kendari. The intervention was implemented through a health book exhibition featuring popular health books, educational visual media, and active reading assistance sessions. Health literacy was measured before and after the intervention using a structured measurement instrument. The results indicated a significant increase in students’ understanding, with the average post-test score increasing by 43.3% compared with the pre-test score. The paired t-test yielded a p-value of 0.000. The findings suggest that health book exhibitions may be effective as a contextual and easily applicable promotive education strategy in school settings. This approach has the potential to serve as a sustainable health literacy intervention model for junior high schools.